Innovative product design for students-enterprises linked projects. (1st January 2011) - Bigand, Michel; Deslée, Carine; Yim, Pascal
The training programme of European Technological Institute of Entrepreneurship and Management (ITEEM), a French graduate engineering school, includes a design and achievement project of product/service for an enterprise achieved by a team of five students. An original creative and innovative approach is presented. Innovation has a big role in the ITEEM programme, because the objective is to train future entrepreneurs in the field of high technology. Each project is followed by a lecturer during the whole process; one of his/her mission is to bring methodological supports for innovation. So, the students have a practical experience of innovative solutions research on a real problematic, and the enterprise discovers new possibilities to develop innovative solutions. By experience, all types of enterprises are interested, but our target is rather the SME (small and medium enterprise) that cannot take on engineers, due to their wage costs. But this approach has also been used in design projects for large enterprises.